Innovative Transport of High Density Thickened Tailings by Means of Hydraulically Actuated MULTISAFE Double Hose-Diaphragm Pump - Naegel, HM (Paste 2009: Proceedings of the Twelfth International Seminar on Paste and Thickened Tailings, 2009)
The handling of high density thickened tailings calls for pumps with maximum safety and minimum downtime. Double hose-diaphragm pumps with overall online condition monitoring provide multiple safety and maximum availability. The particular advantage of this design is the linear flow path, so that it is especially conducive to the handling of aggressive, abrasive and viscous slurries.